(untitled) (El-Wahat Journal for Research and Studies, 2021)
Due To The Importance Of Legitimate Purposes In The Development Of Legal Provisions And Weighting Between Them, The Need For The Jurist Was Urgent, And This Need Appears When The Conflict Of Legitimate Evidence So That The Evidence Is Equal And Can Not Be Combined, Then We Rely On The Purposes Of The Shariah In The Weighting, For That I Felt Dealt With This Subject Weighting Intentions When Ibn Rushd The Grandson Through His Book The Beginning Of Hardworking And The End Of Almnqnad To Show Practically How To Employ And Do This World Galilee Intentions In Weighting Between The Provisions The Research Came In Three Demands: First, The Definition Of The Terms Of The Title, Weighting The Purposes, And The Second Dealt With The Consideration Of The Purposes Of Ibn Rushd Points: 1 - Provisions Of The Law Between Worship And Reasoning 2 - The Words Related To The Purposes Of Ibn Rushd 3 - Adapt The Provisions To The Purposes Of A Statement Activation Of The Purposes, And The Third- A Statement Of Weightings Makassed Examples, And Then A Conclusion Included The Most Important Results.